(untitled) (Revista de História Regional, 2007)
The present article objects to reflecting about sociability presented by the members of the Centro de Tradições Gaúchas Vila Velha, the first representative of the gauchos traditionalism to be created out of the original state of this movement. We try to focus on the analysis of the stabilished social relations among the CTG members, institution which simbolized their adherence to the gaucho identity and to traditional behavior codes, keeping in mind that inside of it there was a very strict environment where the familiar ambient and the customs shold be kept.